(untitled) (Acta Entomologica Serbica, 2012)
This paper includes the first study of the distribution of Heteroptera in the ecologically highly threatened catchment area of Sitnica River. It is the only recipient for large amounts of waste water which alter its ecological characteristics. There were 12 species of aquatic and semiaquatic bugs recorded in 88 samples: Nepa cinerea Linnaeus, Corixa punctata (Illiger), Sigara (Pseudovermicorixa) nigrolineata (Fieber), Sigara (Retrocorixa) limitata (Fieber), Sigara (Sigara) striata (Linnaeus), Sigara (Subsigara) iactans Jansson, Sigara (Vermicorixa) lateralis (Leach), Notonecta (Notonecta) glauca Linnaeus, Notonecta (Notonecta) viridis Delcourt, Aphelocheirus (Aphelocheirus) aestivalis (Fabricius), Mesovelia furcata Mulsant & Rey, Velia (Plesiovelia) caprai Tamanini. Sigara (Subsigara) iactans is a new species for Serbian fauna. Among the collected specimens three species stood out: Sigara (Sigara) striata, Sigara (Subsigara) iactans and Aphelocheirus (Aphelocheirus) aestivalis.This paper includes the first study of the distribution of Heteroptera in the ecologically highly threatened catchment area of Sitnica River. It is the only recipient for large amounts of waste water which alter its ecological characteristics. There were 12 species of aquatic and semiaquatic bugs recorded in 88 samples: Nepa cinerea Linnaeus, Corixa punctata (Illiger), Sigara (Pseudovermicorixa) nigrolineata (Fieber), Sigara (Retrocorixa) limitata (Fieber), Sigara (Sigara) striata (Linnaeus), Sigara (Subsigara) iactans Jansson, Sigara (Vermicorixa) lateralis (Leach), Notonecta (Notonecta) glauca Linnaeus, Notonecta (Notonecta) viridis Delcourt, Aphelocheirus (Aphelocheirus) aestivalis (Fabricius), Mesovelia furcata Mulsant & Rey, Velia (Plesiovelia) caprai Tamanini. Sigara (Subsigara) iactans is a new species for Serbian fauna. Among the collected specimens three species stood out: Sigara (Sigara) striata, Sigara (Subsigara) iactans and Aphelocheirus (Aphelocheirus) aestivalis.